2018
DOI: 10.15252/embj.201898997
|View full text |Cite
|
Sign up to set email alerts
|

Shelterin promotes tethering of late replication origins to telomeres for replication‐timing control

Abstract: DNA replication initiates at many discrete loci on eukaryotic chromosomes, and individual replication origins are regulated under a spatiotemporal program. However, the underlying mechanisms of this regulation remain largely unknown. In the fission yeast , the telomere-binding protein Taz1, ortholog of human TRF1/TRF2, regulates a subset of late replication origins by binding to the telomere-like sequence near the origins. Here, we showed using a/LacI-GFP system that Taz1-dependent late origins were predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…These membrane-less structures are formed in discrete nuclear zones with a high density of proteins and nucleic acids that establish cooperative interactions between them. For instance, a recent study has revealed how a group of subtelomeric origins in fission yeast are tethered by shelterin components to a local domain enriched in Rif1 and protein phosphatase 1, imposing late replication (Ogawa et al, 2018). The proteins that recognize replication origins, ORC and CDC6, also serve as molecular chaperones capable of attracting and assembling many additional proteins to the factory core, including CDT1, MCM, CDC45, GINS, PCNA, and DNA polymerases that establish multiple contacts between them.…”
Section: Discussionmentioning
confidence: 99%
“…These membrane-less structures are formed in discrete nuclear zones with a high density of proteins and nucleic acids that establish cooperative interactions between them. For instance, a recent study has revealed how a group of subtelomeric origins in fission yeast are tethered by shelterin components to a local domain enriched in Rif1 and protein phosphatase 1, imposing late replication (Ogawa et al, 2018). The proteins that recognize replication origins, ORC and CDC6, also serve as molecular chaperones capable of attracting and assembling many additional proteins to the factory core, including CDT1, MCM, CDC45, GINS, PCNA, and DNA polymerases that establish multiple contacts between them.…”
Section: Discussionmentioning
confidence: 99%
“…In fission yeast, the shelterin complex (also called telosome) is involved in RT regulation of a subgroup of late origins through Rif1. Shelterin can recruit Rif1 on telomeric DNA, as Taz1 does, and also brings late-replicating regions into the proximity of Rif1 (Tazumi et al 2012;Ogawa et al 2018;Kanoh and Ishikawa 2001). Moreover, Rap1 and Poz1 (two members of the shelterin complex) depletion can impact RT in an indirect manner.…”
Section: Origins Usage and Replication Timingmentioning
confidence: 99%
“…Furthermore, replication origins are active even in heterochromatin where lower accessibility likely makes licensing and origin activation challenging. Some proteins that are not required at origins in other genomic regions, such as ORCA and shelterin , are important for licensing heterochromatin or telomeres. Considering the complexity of the eukaryotic genome, it is remarkable that enough origins are licensed in G1 to ensure the entire genome is usually replicated in S phase with few problems.…”
Section: G1: Preparing Dna For S Phasementioning
confidence: 99%